Synthesis, molecular modelling and biological activity of some pyridazinone derivatives as selective human monoamine oxidase-B inhibitors - Ozdemir, Zeynep; Alagoz, Mehmet Abdullah; Uslu, Harun; Karakurt, Arzu; Erikci, Acelya; Ucar, Gulberk; Uysal, Mehtap (Springer Heidelberg, 2020)
Background Since brain neurotransmitter levels are associated with the pathology of various neurodegenerative diseases like Parkinson and Alzheimer, monoamineoxidase (MAO) plays a critical role in balancing these neurotransmitters in the brain. MAO isoforms appear as promising drug targets for the development of central nervous system agents. Pyridazinones have a broad array of biological activities. Here, six pyridazinone derivatives were synthesized and their human monoamine oxidase inhibitory activities were evaluated by molecular docking studies, in silico ADME prediction and in vitro biological screening tests. Methods The compounds were synthesized by the reaction of different piperazine derivatives with 3 (2H)-pyridazinone ring and MAO-inhibitory effects were investigated. Docking studies were conducted with Maestro11.8 software. Results Most of the synthesized compounds inhibited hMAO-B selectively except compound 4f. Compounds 4a-4e inhibited hMAO-B selectively and reversibly in a competitive mode. Compound 4b was found as the most potent (k(i)=0.0220.001 mu M) and selective (SI (Ki (hMAO-A/hMAO-B))=206.82) hMAO-B inhibitor in this series. The results of docking studies were found to be consistent with the results of the in vivo activity studies. Compounds 4a-4e were found to be non-toxic to HepG2 cells at 25 mu M concentration. In silico calculations of ADME properties indicated that the compounds have good pharmacokinetic profiles. Conclusion It was concluded that 4b is possibly recommended as a promising nominee for the design and development of new pyridazinones which can be used in the treatment of neurological diseases.
Keywords: Pyridazinone; Monoamine oxidase inhibition; Molecular docking